INTERPRETATION OF MYTHS IN THE FILM THE STORY OF THE JAVA LAND OF MERAPI - Nur Izzah Islamy; Muhammad Irfan Riyadi (UIN Kiai Ageng Muhammad Besari Ponorogo, 2024)
One type of mass media that captivates viewers both with the content and meaning of what they see is film. The theoretical significance of the story of Merapi Island in Java, as well as its use. The purpose of the study of the words